2011
DOI: 10.1002/clc.21009
|View full text |Cite
|
Sign up to set email alerts
|

How Healthy Were the Arteries of Phidippides?

Abstract: Subacute and chronic cardiac adaptations to marathon running may increase risk for sudden death. Herein, it is proposed that cardiac arrhythmogenic remodeling resulting from prolonged strenuous exertion may also have a systemic vascular component. Marathon running reduces coronary perfusion pressure and causes acute endothelial damage, possibly via altering concentrations of circulating angiogenic growth factors with novel vasoregulatory properties. Marathon runners have increased arterial stiffness and augmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 39 publications
0
17
0
2
Order By: Relevance
“…Hypertension rates and prevalence of other biological cardiovascular right factors are reduced in athletes compared with sedentary individuals. Thus the transient increases in blood pressure, inflammation, and other factors listed by Heffernan (2011) during prolonged and intensive exercise may not be as harmful to the arteries of endurance athletes as indicated when considered within the context of overall favorable chronic effects. In support, van de Laar et al (2010) in a cohort study of 373 subjects showed that lifetime vigorous but not light-to-moderate physical activity predicted reduced rates for arterial stiffness.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Hypertension rates and prevalence of other biological cardiovascular right factors are reduced in athletes compared with sedentary individuals. Thus the transient increases in blood pressure, inflammation, and other factors listed by Heffernan (2011) during prolonged and intensive exercise may not be as harmful to the arteries of endurance athletes as indicated when considered within the context of overall favorable chronic effects. In support, van de Laar et al (2010) in a cohort study of 373 subjects showed that lifetime vigorous but not light-to-moderate physical activity predicted reduced rates for arterial stiffness.…”
Section: Discussionmentioning
confidence: 95%
“…Heffernan (2011) has proposed that the cyclic stress imposed by heavy exertion reduces coronary perfusion pressure, causes acute endothelial damage, and alters angiogenic growth factors, all of which lead to increased arterial stiffness. Studies, however, do not consistently support this assertion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The beneficial effects of regular exercise and the potential cardiovascular risk of acute prolonged exercise have been discussed as the “paradox of exercise,” and previous studies have tried to put the risk of marathon running into perspective . Whether or not prolonged excessive endurance exercise negatively affects vascular function is a matter of ongoing debate …”
Section: Introductionmentioning
confidence: 99%
“…6 Whether or not prolonged excessive endurance exercise negatively affects vascular function is a matter of ongoing debate. 7 Arterial stiffness quantified by the assessment of the carotid-femoral pulse wave velocity (PWV) is considered to be a valid vascular biomarker. PWV has proven its predictive power for cardiovascular and all-cause mortality in populations of different age and health status.…”
mentioning
confidence: 99%